Validation of the Pull-Back Method for Dynamic Tensile Strength Characterization in Unidirectional Reinforced Concrete - Xinlu Yu; Junfeng Zhang; Junhui Gu (Applied Sciences)
The pull-back method for determining dynamic tensile strength assumes one-dimensional stress wave propagation and material homogeneity. This study validates these assumptions for unidirectional reinforced concrete (UDRC) through experiments and numerical simulations. Split Hopkinson pressure bar tests were conducted on plain concrete, plain UDRC, and deformed UDRC specimens containing a central 6 mm steel bar. Ultra-high-speed digital image correlation at 500,000 fps enabled precise local strain rate measurements (3 s−1 to 55 s−1) at fracture locations. Finite element simulations revealed that while reinforcement induces localized multi-axial stresses near the steel–concrete interface, the bulk concrete maintains predominantly uniaxial stress conditions. Experimental results showed less than 1% variation in pull-back velocity between specimen types. Statistical analysis confirmed a unified strain rate-strength relationship: <semantics>σspall=4.1+4.7log10(<mover accent="true">ε˙</mover>)</semantics><semantics>MPa</semantics>, independent of reinforcement configuration (ANCOVA: <semantics>p=0.2182</semantics> for interaction term). The dynamic tensile strength is governed by concrete matrix properties rather than reinforcement type. These findings are the first to experimentally and numerically validate the pull-back method’s applicability to UDRC systems, establishing that dynamic tensile failure is matrix-dominated and enabling simplified one-dimensional analysis for reinforced concrete under impact.